KEY FACTORS INFLUENCING TREE PLANTING DECISIONS OF HOUSEHOLDS: A CASE STUDY IN HOA BINH PROVINCE - Dinh Hai, Le; Thanh Huong, Pham (Journal of Forestry Science and Technology, 2018)
In coping with significant deforestation and forest degradation, currently in Kim Boi district, Hoa Binh province, and massive reforestation projects have been implemented. However, when remarkable attempts and investments have been made in reforestation, interaction of household characteristics and socio-economic factors with smallscale tree planting decision are still little understood. In this study, we survey 150 households (including 75 households with tree planting and 75 households without tree-planting) in Nuong Dam commune, Kim Boi district, Hoa Binh province. The results of stepwise binary logistic regression analysis indicate that the factors, including: Accessibility to Plantation Sites, Forestland Area, Investment Capital, and Knowledge on Silviculture have a significant effect on household’s decision on tree planting in the study area. The study results may provide the basis for proposing solutions to strengthen tree planting of households in the study area.